A direct comparison of the effects of imagery and action observation on hitting performance - Neuman, B.; Gray, R. (Movement & Sport Sciences - Science & Motricité, 2013)
Novice and experienced baseball players participated in one of two mental preparation conditions (observation, imagery) or a control group. Each participant completed three directional hitting tasks: pull hit, opposite-field hit, and sacrifice fly. Number of hits was significantly higher for both observation and imagery than for the control group. Experienced players demonstrated significantly larger effects of both preparation techniques. The effects of experience and preparation technique also varied significantly with task difficulty. These effects were significantly mediated by changes in batting kinematics. Imagery and action observation can improve hitting ability with the optimal method depending on skill-level and task difficulty.